2021
DOI: 10.3390/s21165329
|View full text |Cite
|
Sign up to set email alerts
|

Soft System Based on Fiber Bragg Grating Sensor for Loss of Resistance Detection during Epidural Procedures: In Silico and In Vivo Assessment

Abstract: Epidural analgesia represents a clinical common practice aiming at pain mitigation. This loco-regional technique is widely used in several applications such as labor, surgery and lower back pain. It involves the injections of anesthetics or analgesics into the epidural space (ES). The ES detection is still demanding and is usually performed by the techniques named loss of resistance (LOR). In this study, we propose a novel soft system (SS) based on one fiber Bragg grating sensor (FBG) embedded in a soft polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Carotenuto et al reported [ 13 ] and tested [ 2 ] a method based on an FBG mounted inside the needle that converts the tip force into a detectable strain. Similar work was recently proposed by De Tommasi et al [ 14 ] using a single FBG assembled in the epidural needle. Ambastha et al [ 15 ] also proposed an FBG-sensing method adapted to lumbar insertion and validated it on an animal model.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Carotenuto et al reported [ 13 ] and tested [ 2 ] a method based on an FBG mounted inside the needle that converts the tip force into a detectable strain. Similar work was recently proposed by De Tommasi et al [ 14 ] using a single FBG assembled in the epidural needle. Ambastha et al [ 15 ] also proposed an FBG-sensing method adapted to lumbar insertion and validated it on an animal model.…”
Section: Introductionsupporting
confidence: 56%
“…Epidural anesthesia is characterized by a high variability of results, as the layers encountered by the needle as it progresses from the outer skin to the ES vary in thickness and stiffness and, therefore, different patterns are observed [ 14 ]. So far, perceptive methods (loss of resistance, hanging drop) are in use to support clinicians in the task [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The injections are used to deliver steroids, and sometimes local anesthetics, to the epidural space, directly to the site that causes the pain using a caudal, interlaminar or transforaminal approach [ 9 ]. The epidural injection is a well-founded anesthetic and analgesic technique; moreover, nowadays, new technological devices can help anesthesiologists to learn and to administer it [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Even though it is still not clear which type of conservative intervention is superior, several studies have proved that an ESI is able to increase patients’ quality of life, relieve lumbosacral radicular pain and finally, reduce or delay more invasive interventions, such as spinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers promote the introduction of smart devices to support anesthesiologists during the procedure, allowing more accurate detection of the ES and reducing the risk of adverse events caused by a wrong procedure [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Some of these devices are commercially available and intended to provide visual and/or acoustic feedback to the operator as the ES is reached by measuring pressure during tissue crossing.…”
Section: Introductionmentioning
confidence: 99%